Cold Waves In Northwest India - SIRCAR, N. C. RAT; DATAR, S. V. (MAUSAM, 1963)
During the winter months, northwest India experiences cold waves after the passage of western disturbances across the same area. These cold waves may be broadly classified under two categories, viz (1) dry cold waves and (2) moist cold waves. When the area is in the grip of a dry cold wave, there is no deterioration in the morning visibility and the aviation activity is not affected in any way. On the other hand, widespread fog occurs in the area when it experiences moist cold wave and this dislocates air traffic very badly. In the note, the conditions favourable for Occurrence of dry fog as well as moist fog have been discussed and illustrated. The typical instances included in the note will be found useful to forecaster in predicting for occurrences of widespread fog of persisting type in NW India.